2018
DOI: 10.1007/s40618-018-0947-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of HRAS and CDK4/6 inhibitors in anaplastic thyroid cancer cell lines

Abstract: This study suggests that TIP and PD, which are currently in clinical trials for other types of cancer, may play a relevant role in ATC treatment, depending on the specific tumour molecular profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Moreover, the treatment of thyroid cancer cells with the CDK4/6 inhibitor palbociclib (PD-0332991) induces a consistent antiproliferative effect [76]. In keeping with our results, other groups have confirmed the efficacy of palbociclib in in vitro and in vivo preclinical models of TC, also in combination with a PI3K/mTOR inhibitor to bypass mechanisms of therapy resistance [89][90][91]. On the whole, we are confident that the evidence that cyclin D1 represents TC cell vulnerability may prompt preclinical and clinical studies employing CDK4/6 inhibitors for treatment of TC.…”
Section: Validation Of Noa Targetssupporting
confidence: 86%
“…Moreover, the treatment of thyroid cancer cells with the CDK4/6 inhibitor palbociclib (PD-0332991) induces a consistent antiproliferative effect [76]. In keeping with our results, other groups have confirmed the efficacy of palbociclib in in vitro and in vivo preclinical models of TC, also in combination with a PI3K/mTOR inhibitor to bypass mechanisms of therapy resistance [89][90][91]. On the whole, we are confident that the evidence that cyclin D1 represents TC cell vulnerability may prompt preclinical and clinical studies employing CDK4/6 inhibitors for treatment of TC.…”
Section: Validation Of Noa Targetssupporting
confidence: 86%
“…Furthermore, the identification of cell cycle gene alterations, such as CCNE1 amplifications, suggest that CDK inhibitors (such as CDK4/6 inhibitors) may be a viable treatment option. Preclinical studies in ATC cell lines and ATC xenograft models further support this [71,72,73]. These findings remain to be extended to clinical trials.…”
Section: Discussionmentioning
confidence: 65%
“…A trial underway showed a 20% improvement in tumour size with use of a new NTRK inhibitor entrectinib. Tipifarnib ( HRAS inhibitor) and palbociclib (cyclin D-cyclin-dependent kinase 4/6 inhibitor), both also currently being investigated, have shown reduction in tumour size [ 163 ]. Further development in targeted therapy for ATCs is required.…”
Section: Tumour Microenvironment and Programmed Cell Death 1 Ligand 1 (Pd-l1) Expressionmentioning
confidence: 99%